Developing a Financial Sustainability Model of the Performance Indicators Applied by Jordan Water Company (Miyahuna) - Owais, Lubna; T. Kiss, Judit (International Journal of Engineering and Management Sciences, 2020)
Jordan is now facing real challenges to satisfy the current population water needs due to limited resources. Moreover, unfortunately, as a result of the increased demand for water in developing countries, water resources become scarce, thus, the sustainable management of water resources is very important everywhere and especially in these areas. The Ministry of Water and Irrigation in Jordan is aiming to improve both its quality of service and financial sustainability, therefore, it started to apply the performance measurement system developed by the International Water Association (IWA) to monitor its performance towards achieving these goals. In this article, a model connecting a financial sustainability indicator (operating cost coverage ratio) with other performance indicators applied by the ministry is developed. To assess the performance indicators and to build the model secondary data are collected from the targeted company, the data are analyzed using SPSS and Excel computer programs. Non-revenue water (NRW), speed of repair of bursts, and training per employee are found to be the indicators that have a major impact on Miyahuna’s financial sustainability, the NRW is found to have a negative relationship with the financial sustainability, whereas the other two indicators have a positive relationship. As a conclusion, reducing the NRW and increasing both the speed of repair and training per employee are recommended, by applying some methods that continuously diagnose problems in the water systems and defining clear and strict policies to control the water theft. Furthermore, using Active Leakage Control (ALC) methods, providing the needed equipment, tools and resources, and adopting new methods for training.